Renal Mucormycosis: A Rare and Potentially Lethal Complication of Kidney Transplantation - SreyRam Kuy; Chun He; David C. Cronin (Case Reports in Transplantation)
Renal mucormycosis is a rare and potentially lethal complication of kidney transplantation. We describe two cases of renal mucormycosis following deceased donor kidney transplantation. This is the second report of renal mucormycosis following kidney transplantation in the United States, and the first case of renal mucormycosis infection presumed to be of recipient origin. Case A had an early presentation of mucormycosis isolated to the kidney allograft. He had an unexpected rise in serum creatinine and leukocytosis necessitating allograft biopsy which showed mucormycosis. He underwent transplant nephrectomy on posttransplant day 11, was treated with amphotericin B, and discharged home on posttransplant day 22. Case B had a late presentation of renal mucormycosis, preceded by a cutaneous manifestation. One year after kidney transplantation he had a nonhealing knee ulcer which on biopsy showed cutaneous mucormycosis. Treatment included aggressive debridement and amphotericin B. Allograft biopsy showed mucormycosis, necessitating transplant nephrectomy. He was discharged to a rehabilitation facility and died from noninfectious causes. Review of the published literature of renal mucormycosis cases following kidney transplantation reveals a mortality rate of more than 50%. The key to successful outcome is early recognition, prompt institution of surgical debridement of all infected tissue, and appropriate antifungal therapy.